2022
DOI: 10.1111/mpp.13208
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐responsive factor ERF114 mediates fungal pathogen effector PevD1‐induced disease resistance in Arabidopsis thaliana

Abstract: APETALA2/ethylene‐responsive factor (AP2/ERF) family transcription factors are well‐documented in plant responses to a wide range of biotic and abiotic stresses, but their roles in mediating elicitor‐induced disease resistance remains largely unexplored. PevD1 is a Verticillium dahliae secretory effector that can induce disease resistance in cotton and tobacco plants. In our previous work, Nicotiana benthamiana ERF114 (NbERF114) was identified in a screen of genes differentially expressed in response to PevD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…4a). PAL1 has been thoroughly related to plant defense responses [31,32,17]. Our metabolomic analysis further corroborated transcriptomic ndings as we found signi cant enrichment of the phenylpropanoid pathway in the roots of Pima-S6 compared to Pima S-7.…”
Section: Discussionsupporting
confidence: 85%
“…4a). PAL1 has been thoroughly related to plant defense responses [31,32,17]. Our metabolomic analysis further corroborated transcriptomic ndings as we found signi cant enrichment of the phenylpropanoid pathway in the roots of Pima-S6 compared to Pima S-7.…”
Section: Discussionsupporting
confidence: 85%
“…Most DEGs of ethylene-responsive factors were upregulated in the double inoculation of AMF and C. camelliae , possibly implying that the transcription factors were one of the key pathways to resist the pathogen after AMF inoculation. Ethylene-responsive factors are excellent candidates for developing plant resistance to anthracnose and other fungal diseases ( Svoboda et al., 2021 ), and loss of ERF114 function caused impaired disease resistance ( Li et al., 2022 ). Therefore, future research could be focused on this field.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ERF114 positively regulates the immunity of N. benthamiana plants against bacterial speck [ P. syringae pv. tomato (Pst)] DC3000 by modulating the accumulation of lignin and salicylic acid induced by the effector PevD1 (Li et al., 2022). In this study, we showed that infection with R. solanacearum and the exogenous application of ABA both significantly induce the accumulation of ERF098 transcripts (Figure S8).…”
Section: Discussionmentioning
confidence: 99%